1991
DOI: 10.1148/radiology.178.1.1984327
|View full text |Cite
|
Sign up to set email alerts
|

Detection of gastric erosions: comparison of biphasic radiography with fiberoptic endoscopy.

Abstract: Biphasic radiography was compared with fiberoptic endoscopy in detecting gastric erosions in a prospective, blinded study of 385 patients with dyspepsia. Because no absolute standard was available for the comparison, since histologic confirmation of all erosions was not possible, the kappa statistic was used to compare results from both modalities. Flat (incomplete) erosions were detected with endoscopy only and were considered to be present in 42 patients (11.2%). Varioliform (complete) erosions were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An important reason for patients with dyspeptic symptoms to consult a physician is fear of having a malignancy. Negative upper gastrointestinal endoscopy results can appease these fears, but there are other methods to reassure patients, such as upper gastrointestinal radiology, because the diagnostic yield of radiology is comparable with endoscopy for upper gastrointestinal malignancies 26 . The only disadvantage is that, if a suspicious lesion is detected, the patient should be referred for upper gastrointestinal endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important reason for patients with dyspeptic symptoms to consult a physician is fear of having a malignancy. Negative upper gastrointestinal endoscopy results can appease these fears, but there are other methods to reassure patients, such as upper gastrointestinal radiology, because the diagnostic yield of radiology is comparable with endoscopy for upper gastrointestinal malignancies 26 . The only disadvantage is that, if a suspicious lesion is detected, the patient should be referred for upper gastrointestinal endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Negative upper gastrointestinal endoscopy results can appease these fears, but there are other methods to reassure patients, such as upper gastrointestinal radiology, because the diagnostic yield of radiology is comparable with endoscopy for upper gastrointestinal malignancies. 26 The only disadvantage is that, if a suspicious lesion is detected, the patient should be referred for upper gastrointestinal endoscopy. However, previous studies have indicated that gastrointestinal malignancies are only found in a minority of patients (< 5%) who the general practitioner refers a need for endoscopy or radiology.…”
Section: Discussionmentioning
confidence: 99%